Prophylactic Palmitoylethanolamide Prolongs Survival and Decreases Detrimental Inflammation in Aged Mice With Bacterial Meningitis - Heide, Ev Christin; Bindila, Laura; Post, Julia Maria; Malzahn, Dörthe; Lutz, Beat; Seele, Jana; Nau, Roland; Ribes, Sandra (Frontiers in Immunology, 2018)
Easy-to-achieve interventions to promote healthy longevity are desired to diminish the incidence and severity of infections, as well as associated disability upon recovery. The dietary supplement palmitoylethanolamide (PEA) exerts anti-inflammatory and neuroprotective properties. Here, we investigated the effect of prophylactic PEA on the early immune response, clinical course, and survival of old mice after intracerebral E. coli K1 infection. Nineteen-month-old wild type mice were treated intraperitoneally with two doses of either 0.1 mg PEA/kg in 250 µl vehicle solution (n = 19) or with 250 µl vehicle solution only as controls (n = 19), prior to intracerebral E. coli K1 infection. Survival time, bacterial loads in cerebellum, blood, spleen, liver, and microglia counts and activation scores in the brain were evaluated. We measured the levels of different cytokines and chemokines in cerebellum and spleen, as well as of bioactive lipids in serum in PEA- and vehicle-treated animals 24 h after infection. In the absence of antibiotic therapy, the median survival time of PEA-pre-treated infected mice was prolonged by 18 h compared to mice of the vehicle-pre-treated infected group (P = 0.031). PEA prophylaxis delayed the onset of clinical symptoms (P = 0.037). This protective effect was associated with lower bacterial loads in the spleen, liver, and blood compared to those of vehicle-injected animals (P ≤ 0.037). PEA-pre-treated animals showed diminished levels of pro-inflammatory cytokines and chemokines in spleen 24h after infection, as well as reduced serum concentrations of arachidonic acid and of one of its metabolites, 20-hydroxyeicosatetraenoic acid. In the brain, prophylactic PEA tended to reduce bacterial titers and attenuated microglial activation in aged infected animals (P = 0.042). Our findings suggest that prophylactic PEA can counteract infection-associated detrimental responses in old animals. Accordingly, PEA slowed the onset of infection symptoms and prolonged the survival of old infected mice. In a clinical setting, prophylactic administration of PEA might extend the potential therapeutic window where antibiotic therapy can be initiated to rescue the elderly patient.